STUDI PENGGUNAAN ANTIMALARIA PADA PENDERITA MALARIA DI INSTALASI RAWAT INAP BLU RSUP Prof. Dr. R. D. KANDOU MANADO PERIODE JANUARI 2013-MEI 2013 - Rumagit, Novia Akwila; Tjitrosantoso, Heedy; Wiyono, Weny I (PHARMACON, 2013)
ABSTRACT Malaria is parasite infectious diseases group of Plasmodium which live in human red blood cell and can be transmitted by a female Anopheles bites. Malaria were classified as one of the most dangerous infectious diseases which cause death. In North Sulawesi, malaria is an endemic diseases because it’s a tropical area, and so susceptible to this disease. Treatment of malaria is to obtain clinical and parasitologic recovery. The objectives of this research were to find out the characteristic of malaria and the use of antimalaria drugs on patient with malaria. This research is a descriptive survey with retrospective sampling on 68 medical record of patient with malaria treatment. Obtained data shows that there are three variant of malaria, falciparum malaria (66,2%), vivax malaria (26,5%), mixed malaria (7,4%). Artesunat-amodiakuin-primakuin in an ACT (Artemisinin Combination Treatment) that mostly used as malaria drug. Keywords: Plasmodium, red blood cell, malaria, antimalaria